2021
DOI: 10.1016/j.nutos.2021.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of artificially administered nutrition and hydration in different age groups among patients with advanced cancer admitted to palliative care units

Abstract: Background & Aims: The prevalence of artificially administered nutrition and hydration (AANH) in different age groups among patients with advanced cancer remains unknown. The present study investigated the current utilization of AANH according to age groups in palliative care units. Methods: This was a secondary analysis of a prospective cohort study. We obtained information on primary nutritional administration routes during the first week of admission and data on the averaged calorie sufficiency rate or tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In a recent study determining the utilization of artificially administered nutrition classified to age groups in palliative care units, patients were categorized according to the average calorie sufficiency rate or total calorie intake. The proportions of the patients categorized into ≥50% or ≥ 500 kcal/day were 23.5% in the 60–74 years group and 14% in the 75–89 years group during the first week of admission 39 . In another study identifying the effects of enteral tube feeding (ETF) and parenteral nutrition and hydration (PNH) on survival in palliative care patients with head and neck cancer (mean age of 71.5 ± 12.1 years), 48.9% of the patients had a ≥ 50% or 500 kcal/day calorie sufficiency rate or total calorie intake on day seven 40 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent study determining the utilization of artificially administered nutrition classified to age groups in palliative care units, patients were categorized according to the average calorie sufficiency rate or total calorie intake. The proportions of the patients categorized into ≥50% or ≥ 500 kcal/day were 23.5% in the 60–74 years group and 14% in the 75–89 years group during the first week of admission 39 . In another study identifying the effects of enteral tube feeding (ETF) and parenteral nutrition and hydration (PNH) on survival in palliative care patients with head and neck cancer (mean age of 71.5 ± 12.1 years), 48.9% of the patients had a ≥ 50% or 500 kcal/day calorie sufficiency rate or total calorie intake on day seven 40 .…”
Section: Discussionmentioning
confidence: 95%
“…The proportions of the patients categorized into ≥50% or ≥ 500 kcal/day were 23.5% in the 60-74 years group and 14% in the 75-89 years group during the first week of admission. 39 In another study identifying the effects of enteral tube feeding (ETF) and parenteral nutrition and hydration (PNH) on survival in palliative care patients with head and neck cancer (mean age of 71.5 ± 12.1 years), 48.9% of the patients had a ≥ 50% or 500 kcal/day calorie sufficiency rate or total calorie intake on day seven. 40 In a previous study, the mean calorie intake of the patients hospitalized in palliative care was 1273 kcal/day.…”
Section: Hazard Ratio 95% Confidence Interval Pmentioning
confidence: 99%
“…Chemotherapy causes nutrition impact symptoms (NIS), such as taste disorder, olfactory disorder, and constipation [ 1 , 2 ], and can aggravate pre-existing nutritional issues [ 3 , 4 ]. Studies have shown that 50–80% of patients with advanced cancer experience cachexia, a systemic metabolic disorder characterized by weight loss and loss of skeletal muscle mass, which affects their quality of life (QOL) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%